2022
DOI: 10.1111/1753-0407.13301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS‐CoV2 on youth onset type 2 diabetes new diagnoses and severity

Abstract: Introduction Initial reports show an increase in youth onset type 2 diabetes during the COVID‐19 pandemic. We aim to expand on existing evidence by analyzing trends over a longer period. Objectives Our study aims to describe change in the amount, severity, and demographics of youth onset type 2 diabetes diagnoses during the COVID‐19 pandemic compared to the five years before. Methods We performed a retrospective cross‐sectional review of yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Rates of prediabetes were increasing in 12‐ to 19‐year‐old youth prior to the pandemic [ 11 ], and the prevalence of prediabetes was greater among 12‐ to 19‐year‐old Black and Hispanic individuals in the 2015 to 2018 NHANES cycles [ 11 ]. Several studies have demonstrated marked increases in type 2 diabetes (T2DM) among adolescents during the pandemic that ranged from 77% to 293%, with greater increases in Black and Hispanic youth compared with White youth [ 12 , 13 , 14 ]. Severe obesity was already present in many of those who developed T2DM [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of prediabetes were increasing in 12‐ to 19‐year‐old youth prior to the pandemic [ 11 ], and the prevalence of prediabetes was greater among 12‐ to 19‐year‐old Black and Hispanic individuals in the 2015 to 2018 NHANES cycles [ 11 ]. Several studies have demonstrated marked increases in type 2 diabetes (T2DM) among adolescents during the pandemic that ranged from 77% to 293%, with greater increases in Black and Hispanic youth compared with White youth [ 12 , 13 , 14 ]. Severe obesity was already present in many of those who developed T2DM [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated marked increases in type 2 diabetes (T2DM) among adolescents during the pandemic that ranged from 77% to 293%, with greater increases in Black and Hispanic youth compared with White youth [ 12 , 13 , 14 ]. Severe obesity was already present in many of those who developed T2DM [ 13 , 14 ]. In the only study, to our knowledge, that examined weight gain immediately prior to diagnosis, weight increased by a median of 11 kg (interquartile range: 6.1‐17.7 kg) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, its incidence increased in Florida from 14.6/100000 pre-pandemic to 16.9/100000 in the first quarter of 2020[ 33 ]. There was a 293% increase in Illinois[ 34 ] and a 225% increase in Wisconsin[ 35 ] compared to the pre-pandemic mean. As expected, the increase was greater among certain racial and ethnic subgroups, particularly among the Hispanic and Black population.…”
Section: Epidemiology Of Type 2 Diabetesmentioning
confidence: 99%
“…Ten were published by a student with a faculty appointment [34][35][36][37][38][39][40][41][42][43]. Overall, there were 3 case reports [34,44,45], one case series [46], 2 editorials [41,43], 2 letters [37,47], 2 review articles [48,49], 7 systematic reviews [35,36,[38][39][40]42,50], 2 retrospective cohort studies [51,52], an evaluation of mobile health applications [53], and a medical education report. [54] One case report noted the subject's race, without further comment [44].…”
Section: Course Evaluation and Student Publicationsmentioning
confidence: 99%
“…All retrospective cohort studies used race as a demographic variable, but there was variability in whether methods of collection were described and what categories were used. One found that Hispanic ethnicity was a risk factor for youth onset type 2 diabetes and discussed limitations of electronic health record data and impact of social determinants of health [51]. Other articles did not present data on race or ethnicity.…”
Section: Course Evaluation and Student Publicationsmentioning
confidence: 99%